2011
DOI: 10.1016/j.apcatb.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of antibiotic sulfamethoxazole by photoelectro-Fenton treatment using activated carbon fiber cathode and under UVA irradiation

Abstract: a b s t r a c tThe mineralization of antibiotic sulfamethoxazole (SMX) of concentrations up to 300 mg L −1 was examined by photoelectro-Fenton (PEF) using an activated carbon fiber (ACF) cathode with UVA (365 nm) irradiation. Comparative mineralization has been studied by different methods: RuO 2 /Ti anodic oxidation (AO), AO in the presence of electrogenerated H 2 O 2 (AO-H 2 O 2 ), AO-H 2 O 2 in the presence of UVA (AO-H 2 O 2 -UVA), and both the electro-Fenton (EF) and PEF processes. PEF treatment at a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(42 citation statements)
references
References 62 publications
3
38
0
1
Order By: Relevance
“…Furthermore, it can be seen in Fig. 8(a) and (b) [40]. Besides, Gonçalves et al [19] reported that amine group and isoxazole ring in SMZ form NH 4 + and NO 3 À ions, respectively.…”
Section: Degradation Productsmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, it can be seen in Fig. 8(a) and (b) [40]. Besides, Gonçalves et al [19] reported that amine group and isoxazole ring in SMZ form NH 4 + and NO 3 À ions, respectively.…”
Section: Degradation Productsmentioning
confidence: 90%
“…[28,29,39], and it has been well known that inorganic ions such as NO 3 À , NH 4 + and SO 4 2À are generated by cleavages of bonds containing N and S atoms during the oxidation treatment [19,40,41]. The toxicity of degradation byproducts may be a matter of concern.…”
Section: Degradation Productsmentioning
confidence: 98%
See 1 more Smart Citation
“…3 shows the effect of different ferrous ion concentrations ranging from 0 to 3.5 mM under EF conditions for the electrolysis of 200 mg/L of cefalexin with an applied current of 6.66 mA/cm 2 , and a pH of 3 for 480 min. The ferrous ion catalyzes the decomposition of H 2 O 2 into the reactive species ( • OH) that oxidize the CEX molecules [9,[32][33][34][35][36] After 8 h of treatment, the TOC removals were 8%, 22%, and 49% for 0, 0.5 and 1 mM of Fe 2+ concentrations, respectively. When the initial concentration of Fe 2+ ions in the solution raised from 0 to 1 mM, a remarkable enhancement in the TOC decay was observed.…”
Section: Effect Of Fe 2+ Concentrationmentioning
confidence: 99%
“…was also reported [61,77] (18)) [59]. It should be noted that the dimerization generally occurs at higher concentration of hydroxyl radicals, and such higher concentration is possible with the higher voltage (or current) applied [79].…”
Section: Bdd Ohmentioning
confidence: 91%